Enhancing the biosynthesis of riboflavin in the recombinant Escherichia coli BL21 strain by metabolic engineering - Fu, Bing; Ying, Junhui; Chen, Qingwei; Zhang, Qili; Lu, Jiajie; Zhu, Zhiwen; Yu, Ping (Frontiers in Microbiology, 2023)
In this study, to construct the riboflavin-producing strain R1, five key genes, ribA, ribB, ribC, ribD and ribE, were cloned and ligated to generate the plasmid pET-AE, which was overexpressed in E. coli BL21. The R1 strain accumulated 182.65 ± 9.04 mg/L riboflavin. Subsequently, the R2 strain was constructed by the overexpression of zwf harboring the constructed plasmid pAC-Z in the R1 strain. Thus, the level of riboflavin in the R2 strain increased to 319.01 ± 20.65 mg/L (74.66% increase). To further enhance ribB transcript levels and riboflavin production, the FMN riboswitch was deleted from E. coli BL21 with CRISPR/Cas9 to generate the R3 strain. The R4 strain was constructed by cotransforming pET-AE and pAC-Z into the R3 strain. Compared to those of E. coli BL21, the ribB transcript levels of R2 and R4 improved 2.78 and 3.05-fold, respectively. The R4 strain accumulated 437.58  14.36 mg/L riboflavin, increasing by 37.17% compared to the R2 strain. These results suggest that the deletion of the FMN riboswitch can improve the transcript level of ribB and facilitate riboflavin production. A riboflavin titer of 611.22 ± 11.25 mg/L was achieved under the optimal fermentation conditions. Ultimately, 1574.60 ± 109.32 mg/L riboflavin was produced through fed-batch fermentation with 40 g/L glucose. This study contributes to the industrial production of riboflavin by the recombinant E. coli BL21.